Consulting with young people about healthcare. Part 2: experience of long-term health conditions. Issue 2 (April 2010) - McCormack, Abi; Norrish, Sara; Parker, Leah; Frampton, Ian
The aim of this study was to provide a qualitative perspective of young people's experiences of long-term illness using an innovative multimedia research methodology. Three young individuals recorded video diaries and were interviewed about their experiences of living with a long-term illness; the resulting footage was edited into a documentary film and showed to local healthcare professionals, commissioners and policy makers. The original unedited interview transcripts were then analyzed by thematic analysis. Four main themes were identified, representing common shared experiences among participants. These were related to coping with their illness, the impact of illness on various aspects of their life, their experiences of healthcare and transitions from pediatric to adult services. While significant efforts are being made to increase the knowledge and understanding of the experiences of long-term illness within the child and adolescent population, there is still much to be learned, as is evident from this direct account of young people's experiences. We identify implications for clinical practice and suggestions for future research using video and information technologies, in light of listening to the young people's stories.